Nunc quid undique ablatum sit ostendunt (Cic. Verr., 2, 4, 132). Images and memory in Cicero’s Verrines - Caminneci, Valentina (Eikón / Imago, 2022)
We propose some considerations on the theme of memory through the reading of Cicero’s Verrines, fundamental sources, with the archaeological ones, for the study of Sicily during the late Republican period. The dispersion caused by the art thefts of Verre constitutes a destructive process of the memory, based on the images, linked inextricably to their context. The message of the Verrines is still actual especially regarded to clandestine trade of artworks.